Silent coronary artery disease in asymptomatic patients with severe aortic stenosis and normal exercise testing. Issue 2 (March 2020) - Banovic, Marko; Iung, Bernard; Brkovic, Voin; Nikolic, Serge; Mitrovic, Predrag; Van Camp, Guy; Penicka, Martin; Simic, Dragan; Kockova, Radka; Aleksandric, Srdjan; Asanin, Milika; Nedeljkovic, Ivana; et al.
Abstract : Objective: There are no data about the prevalence of silent coronary artery disease in asymptomatic severe aortic stenosis patients with normal exercise testing. Importantly, unmasking significant coronary artery disease in patients with aortic stenosis could influence the choice/timing of treatment in these patients. Method: Exercise testing was performed on semi-supine ergobicycle. Cardiopulmonary analysis during exercise testing, echocardiography, and laboratory analysis at rest was done. Standard clinical/electrocardiography criteria were assessed for symptoms/signs of ischemia during/after exercise testing. In patients with normal exercise testing coronary angiography was performed using standard femoral/radial percutaneous approach. Coronary stenosis was considered significant if >70% of vessel diameter or 50%–70% with fractional flow reserve ⩽0.8. Results: Total of 96 patients with normal exercise testing were included (67.6 years, 50.6% males). No patient had any complication or adverse event. The P mean was 52.7 mmHg, mean indexed aortic valve area was 0.36 cm 2 /m 2 and left ventricular ejection fraction, 69.5%. 19/96 patients (19.8%) had significant coronary artery disease on coronary angiography. Multivariate logistic regression analysis revealed brain natriuretic peptide and blood glucose as independent predictors of silent coronary artery disease. Brain natriuretic peptide value of 118 pg/ml had sensitivity/specificity of 63%/73% for predicting coronary artery disease (area under the curve 0.727, P = 0.006). Conclusion: Our results are the first to show that in patients with severe aortic stenosis, normal left ventricular ejection fraction, , and normal exercise testing, significant coronary artery disease is present in as many as 1/5 patients. In such patients, further prospective studies are warranted to address the diagnostic value of brain natriuretic peptide in detecting silent coronary artery disease.